Human nature philosophies and preferences for psychological theories - Webster, Krysta Lynette (2005)
The differences in individual perspectives among college freshmen on both their view of human nature and their personal preferences for psychological theories were investigated in this study. A questionnaire (HNQ) measuring human nature viewpoints was used to determine, for example, individual standpoints on human nature. The following human nature dimensions were used in this study: evil/good,unchangeable/changeable, nurture/nature, determinism/freewill, and pessimism/optimism Scenarios presenting a behavior followed by five explanations for that behavior were used to measure students' preferences for psychological theories.Each of the five explanations represented the following psychological theorists and theories used in this study: Skinner, evolutionary psychological theory, Freud, Maslow,and Kelly. It was hypothesized that individuals who prefer a particular psychological theorist (e.g., Freud, Skinner, etc.) or theory (evolutionary psychological theory) would show similar preferences as that theorist on the five human nature dimensions used in this study (see Table I). A student who believes that people are generally good, that behaviors and traits are changeable, that behaviors and traits are environmentally influenced. that people can choose their behaviors and traits, and a student who has an optimistic viewpoint about humanity would prefer Maslow's theory. The results of this study revealed significant correlations between the nurture/nature dimension and the evolutionary psychological theory, indicating that students who believe that biology determines behaviors and traits prefer the evolutionary psychological theory. None of the other human nature dimensions and psychological theories showed significant correlations. The results of this study also revealed inconsistencies in students' responses to the HNQ and PTQ, which present difficulties in interpreting the results. Nonetheless, the pessimism/optimism dimension demonstrated marginally consistent responses, as well as Freud's psychological theory.